Preparation and characterization by infrared emission spectroscopy and applications of new mineral-based composite materials of biomedical interest. Issue 6 (3rd July 2018) - Mink, Janos; Mihaly, Judith; Nemeth, Csaba; Nemeth, Peter; Drees, Markus; Lokshin, Boris V.; Wolf, Moritz; Butler, Ian S.; Hajba, Laszlo
ABSTRACT: New composite materials based on clay minerals had been prepared by reductive calcination. These materials exhibit very strong infrared (IR) emission at quite low temperatures. The structural properties and emission capabilities of the new materials have been studied by various theoretical and experimental methods. In addition, a brief overview of the medical and other practical applications of IR-emitting materials is presented. The basic principles of IR emission spectroscopy are discussed with special respect to low temperatures (close to human-body temperature). Furthermore, DFT calculations on a kaolinite structure of chemical composition of [Al4 Si4 O8 (OH)16 ] 4− have been performed. The calculated bond distances and IR spectrum are in good agreement with experimental observations. Structural and compositional characterization of the new composite materials have been performed by various structural analytical methods. An interesting effect on the IR phosphorescence of composite samples has been established. After 2 hours of IR light exposure at room temperature from the FT-IR spectrometer, the composite materials exhibited enhanced emission of IR radiation with relaxation time about 40 min. Finally, two practical applications of the composites have been investigated, namely polyamide-based fabrics and rubber preservatives.